An Experimental Study on the use of Fins on Tubes In Shell-and-Tube Heat Exchangers To Improve Thermal Performance - Anandar, Ommy Nurega; Safi’i, Muhamad; Androva, Althesa (Devotion : Journal of Research and Community Service, 2026)
This research is to analyze the efficiency of the heat exchanger with the addition of fins in each tube. In order to see the efficiency of heat exchangers, this research was carried out through heat exchanger machine tests along with the collection of calculation data in the form of equations. This heat exchanger is in the form of shell and tube, which in the shell has eight passes, each pass has eight tubes and each tube has an additional number of fins, two, four and six. The flow of fluids used in heat exchanger research is through cross flow, where the flow of cold fluid will be channeled through a tube inside the shell that is blown by the blower where the speed is regulated to get a different mass rate, there will also be a heat transfer of cold fluid from the hot fluid distributed in the shell. Through the LPG combustion stage, hot fluid is produced for hot fluid. The cold fluid passing through the tube will receive heat from the hot fluid to the rotary dryer. After data calculation, heat exchangers were obtained with 2 fins per tube for an efficiency output of 57.9%, heat exchangers with 4 fins per tube with an output of 58.5%, heat exchangers with 6 fins per tube with an output of 61.4%.